Extended clinical and immunological phenotype and transplant outcome in CD27 and CD70 deficiency - ÖZEN, AHMET OĞUZHAN; BARIŞ, SAFA (AMER SOC HEMATOLOGY, 2020)
Biallelic mutations in the genes encoding CD27 or its ligand CD70 underlie inborn errors of immunity (IEIs) characterized predominantly by Epstein-Barr virus (EBV)-associated immune dysregulation, such as chronic viremia, severe infectious mononucleosis, hemophagocytic lymphohistiocytosis (HLH), lymphoproliferation, and malignancy. A comprehensive understanding of the natural history, immune characteristics, and transplant outcomes has remained elusive. Here, in a multi-institutional global collaboration, we collected the clinical information of 49 patients from 29 families (CD27, n = 33; CD70, n = 16), including 24 previously unreported individuals and identified a total of 16 distinct mutations in CD27, and 8 in CD70, respectively. The majority of patients (90%) were EBV1 at diagnosis, but only similar to 30% presented with infectious mononucleosis. Lymphoproliferation and lymphoma were the main clinical manifestations (70% and 43%, respectively), and 9 of the CD27-deficient patients developed HLH. Twenty-one patients (43%) developed autoinflammatory features including uveitis, arthritis, and periodic fever. Detailed immunological characterization revealed aberrant generation of memory B and T cells, including a paucity of EBV-specific T cells, and impaired effector function of CD81 T cells, thereby providing mechanistic insight into cellular defects underpinning the clinical features of disrupted CD27/CD70 signaling. Nineteen patients underwent allogeneic hematopoietic stem cell transplantation (HSCT) prior to adulthood predominantly because of lymphoma, with 95% survival without disease recurrence. Our data highlight the marked predisposition to lymphoma of both CD27- and CD70-deficient patients. The excellent outcome after HSCT supports the timely implementation of this treatment modality particularly in patients presenting with malignant transformation to lymphoma.
Keywords: EPSTEIN-BARR-VIRUS; STEM-CELL TRANSPLANTATION; MEMORY B-CELLS; T-CELL; COMBINED IMMUNODEFICIENCY; REFERENCE VALUES; EBV; GENERATION; IMMUNITY; CHILDREN